DESMIDIALES (ZYGNEMATOPHYCEAE, STREPTOPHYTA) OF THE QUARRY POND ZAVODSKE – A HOTSPOT OF DESMIDS DIVERSITY IN CHERNIHIV POLESIE, UKRAINE - Shyndanovina, Iryna (Biota. Human. Technology, 2024)
Purpose. Study of the composition of desmids in Zavodske quarry pond (Chernihiv Polesie, Ukraine), preparation of the taxonomical list. Microphotographs illustrating the cells of desmid algae found Ukrainian and their dimensional characteristics are intended to facilitate their identification and can be used for comparative analysis by both Ukrainian and foreign desmidiologists. Methodology. As part of the PhD dissertation, several field research trips were conducted and algological samples were collected in Zavodske quarry pond (8,625 m2, depth 1.5-2 m), located near the village of Zavodske, Dobryana village community, Chernihiv district and region, Ukraine. From the middle to the end of the last century it was used for extraction of the clay for the needs of the local brick-making plant. The samples were examined alive as well as fixed with 4 % formalin for further storage and examination. Water chemical variables (pH and electrical conductivity) were determined by H&M COM-100 and H&M PH-200 portable multimeters. Microscopic examination of the samples was carried out using light microscopes Olympus BX-51 (samples 2018–2021) and Zeiss Imager A2 (samples 2021–2022). The main literature for the definition: Conjugates — Conjugatophyceae. Part 2. Desmids – Desmidiales. In: Identification manual of the freshwater algae of Ukrainian RSR. Palamar-Mordvintseva, 1986; Flora of algae in continental water bodies of Ukraine. Desmid algae. Part 2: Desmidiaceae. Palamar-Mordvintseva, 2005; Desmidiaceenflora von Österreich, Teil 3. Lenzenweger, 1999; Desmids of the Lowlands Mesotaeniaceae and Desmidaceae of the European Lowlands. Coesel & Meesters, 2007. Scientific novelty. This is the first study of the desmid species composition of Zavodske quarry pond. In total 110 taxa were identified, 16 of them recorded for the first time in Ukraine. Conclusions. Zavodske quarry pond is a unique locality with numerous desmids. The number of identified taxa (110 taxa – 11.4 % of the desmidioflora of Ukraine) and part of the newly found in Ukraine (16 out of 110 taxa – 1.65 % of the desmidioflora of Ukraine) are extraordinary and deserves close attention and protection of their habitat.